(untitled) (Journal of Philosophy Culture and Political Science, 2020)
The article describes the technique and results of the study of political discourse using text mining technology with the statistical package R. Unlike traditional content analysis, text mining uses automated methods for processing text in natural languages. The article presents a specific technique of computational operations and an algorithm of visualization. The study aims to study the corpus of texts of the President Address to the Federal Assembly in Russia. The study describes the evolution of the political agenda in post-Soviet Russia within the discourse analysis approach. The study shows that the idea of ‘democracy and human rights’ fails to be the key concepts of public policy in Russia. The presidents of Russia usually stick around 3 common topics: Russia, state, and power. The author approves that text mining allows us to automate part of the research work and it functions as one of the directions for a comprehensive analysis of political discourse. The applied technique can be used to automate research in political linguistics, as well as to study different types of political documents and texts. Key words: text mining, political discourse, president address, political communication, mathematical linguistics.